2010
DOI: 10.1002/jat.1581
|View full text |Cite
|
Sign up to set email alerts
|

Mustard gas toxicity: the acute and chronic pathological effects

Abstract: Ever since it was first used in armed conflict, mustard gas (sulfur mustard, MG) has been known to cause a wide range of acute and chronic injuries to exposure victims. The earliest descriptions of these injuries were published during and in the immediate aftermath of the First World War, and a further series of accounts followed the Second World War. More recently, MG has been deployed in warfare in the Middle East and this resulted in large numbers of victims, whose conditions have been studied in detail at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
114
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(122 citation statements)
references
References 149 publications
(209 reference statements)
5
114
0
Order By: Relevance
“…Earlier studies have shown that ocular exposures to UVB or vesicants results in damage to the corneal epithelium, which involves both acute and chronic keratopathies (Bergmanson, 1990; Ghabili et al , 2010). Depending on dose, inflammation and edema are observed as well as increasing corneal thickness, and sloughing of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that ocular exposures to UVB or vesicants results in damage to the corneal epithelium, which involves both acute and chronic keratopathies (Bergmanson, 1990; Ghabili et al , 2010). Depending on dose, inflammation and edema are observed as well as increasing corneal thickness, and sloughing of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…For the period of use, mustard gas would be fit into a shell and the liquid would be dispersed through the explosion into an aerosol. Signs of exposure of Mustard gas are inflammation and blistering of skin, burning feeling in eyes and blistering in lining of lungs (Ghabili et al, 2010;Graham & Schoneboom, 2013;Solberg et al, 1997). Only 15-20 years after its use were its late-onset, increasingly harmful effects recognized.…”
Section: Mustard Gasmentioning
confidence: 98%
“…(1) Eye and skin damage after absorption through the integument and the ocular surface, respectively (2) Respiratory damage after inhalation (3) Systemic toxicity after Swallow or high exposures, manifested as gastrointestinal, circulatory, renal, and bone marrow toxicity (Blodi, 1971;Borak & Sidell, 1992;Duke-Elder & McFaul, 1972;Ghabili et al, 2010;Solberg et al, 1997). Lung problems are among the most common chronic complications of SM intoxication and are commonly accompanied by deregulated manufacture of pro-inflammatory cytokines.…”
Section: Mustard Gasmentioning
confidence: 98%
“…First of all, the studies that have been published until now lack adequate quantitative data on exposure 2 4. There are two main scenarios for mustard gas exposure: short-term, one-time, high-level exposure in situations like battlefields and chemical industrial accidents; and long-term, low-level exposure in places like production facilities.…”
mentioning
confidence: 99%
“…Young men who survived mustard gas poisoning in those battlefields have been reported to have excess mortality from respiratory cancers 5. Veterans exposed to mustard gas during early and more current interventions have also been reported to suffer from chronic bronchitis 2 4 5…”
mentioning
confidence: 99%